Documento, (Des)Informação e Poder: Memória da Ditadura Militar Brasileira pela Obra "1964 o Brasil entre Armas e Livros" - Soella, Gabriel Meneguelli (2021)
It performs a conceptual ampliation about the notion of document, documentary practices, and regimen of information to analyze from relationship of know and power and of memory and forgetfulness the brazilian military dictatorship (1964-1985) presented on audiovisual document “1964: o Brasil entre armas e livros” from Brasil Paralelo producer, available on YouTube and your relationship with the political authoritarianism on post-truth. In the descriptive and exploratory research of qualitative approach from Information Science, in interdisciplinarity with the History and Sociology, presents theoretical-methodological basis about truth discourses, document, memory, disinformation, negationism, and post-truth, mediated by bibliographic research, documentary research, and critical-genealogical analyses of post-structuralist foucaultean basis of the discourse. It Identify practices from disinformation and negationisms network, on post-truth, demonstrating a double relationship of the post-truth with the illuminist “truth”, whereas it is heiress of the authoritarianist ideas from European colonialist civilizing process and recuse your rational basis in favor of idealized conservative past belief. Presents aspects from negationisms based on structural racism, Nazis anti-Semitism, and in the military anticommunism evidenced in the anti-historical negationism about brazilian military dictatorship (1964-1985) in the cyber space, present in the regimen of (dis)information of the/ in the audiovisual document analyzed. The results demonstrate the (dis)information materiality in authoritarianism favor, strengthened in the post-truth phenomenal, with negationists memories and disinformation practices from military and far-right civil narratives circumscribed in documents created to dispute memory narratives about brazilian military dictatorship (1964-1985). It reflects about relationship between ultraliberal narratives and propagation of memories authoritarianists and counterfactual from far-right. This work highlights disinformation practices used by far-right on Brasil Paralelo movie for affirmation of negationists statements, of knowledge silencing, and of attack against the scientific-academic debates. Thus, it offers interdisciplinary contributes for coping of the authoritarianist negationism and of the disinformation practices enunciated by audiovisual documents in digital platforms on cyber space, fostering new studies.